THE EFFECT OF SELF-CONTROL ON ANTI CORRUPTION ATTITUDE ON STUDENTS OF KINDERGARTENS IN CENTRAL JAVA PROVINCE - Desti Pujiati; Myrnawati Crie Handini; Moch Asmawi (Universitas Muhammadiyah Ponorogo, 2019)
This study aims to determine the effect of self-control on the anti-corruption attitude of kindergarten (TK) students in Central Java province. This Experimental reasearch, the sampling metods was done by multi stage random sampling with probality sampling and it obtained 82 samples of kindergarten students, 41 students of them were selected from the observation with high and low self-control (22 students with high self-control and 22 students with low self-control) in Kindergartens in Central Java Province. Data were obtained using ceklist of observastion sheets for anti corruptions attitude of kindergarten children. The results of the study show that: There is an effect of self-control on anti-corruption attitudes. Students with high self-control have better anti-corruption attitude than students with low self-control. The results showing that the average score of group with self control low 40.3636 and than self control high 47.2273, with the result of t-count 8.005 at the 0.007 level significance.